Travel books to the URSS by Castelnuovo, Varela, Kordon and González Tuñón (1932-1959) (Anclajes, 2023)
The Russian Revolution strengthened the relations of writers between socialist countries and spaces that had not yet had any contact until then, for example, Latin America, generating a new geocultural space for dialogue with each other. This context generates, for critics, a special interest in the Latin American intellectual figures who projects their impressions in travel books to the Soviet Union, on a round trip to his place of origin. From this can be deduced the diachronic analysis of four texts by writers who visited socialist countries between 1932 and 1959, travel books published in Buenos Aires. Specifically, the following works are analyzed: Yo ví…! En Rusia (Castelnuovo, 1932); Un periodista argentino en la Unión Soviética (Varela, 1950); Todos los hombres del mundo son hermanos (González Tuñón, 1954) y 600 millones y uno (Kordon, 1958).
Keywords: Latin-American literature; trips; Southern Cone; URSS; 20º century